Pengaruh Kualitas Pelayanan terhadap Kepuasan Pelanggan Karang Hias (Coral) di CV. Bali Samudra Anugrah - Mage’virawati; Andi Baso Adil Natsir; Yusri Muhammad Yusuf (Pusat Riset dan Inovasi Nasional, 2024)
Service quality management is certainly important in today's increasingly competitive business world. This, of course, is inseparable from the competition of business people in providing services that are guided by meeting customer needs that are able to exceed customer expectations. Customers who meet their needs and feel that the service provided by the service provider exceeds what they expect, then there will be a sense of satisfaction having used the service from the provider. The purpose of this study isto find out the influence of the quality of ornamental corals and how much the service quality affects customer satisfaction in CV. Bali Samudra Anugrah. The type of research used is Quantitative. The data sources used came from Primary Data and Secondary Data with the research methods used, namely questionnaires, literature studies and observations. Hresults of research on the impact of service quality on customer satisfaction in CV. Bali Samudra Anugrah, concluded that there is a significant influence between service quality and customer satisfaction. Based on several test results such as simple linear regression analysis, it was found that the variables of service quality and customer satisfaction showed a positive relationship. The results of this research analysis also show that each variable makes a great contribution to customer satisfaction. Based on several test results such as simple linear regression analysis, it was found that the variables of service quality and customer satisfaction showed a positive relationship. The results of this research analysis also show that each variable makes a great contribution to customer satisfaction. ,